Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jpm11111089
|View full text |Cite
|
Sign up to set email alerts
|

Potential Prognostic Biomarkers of NIMA (Never in Mitosis, Gene A)-Related Kinase (NEK) Family Members in Breast Cancer

Abstract: Breast cancer remains the most common malignant cancer in women, with a staggering incidence of two million cases annually worldwide; therefore, it is crucial to explore novel biomarkers to assess the diagnosis and prognosis of breast cancer patients. NIMA-related kinase (NEK) protein kinase contains 11 family members named NEK1-NEK11, which were discovered from Aspergillus Nidulans; however, the role of NEK family genes for tumor development remains unclear and requires additional study. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 147 publications
0
31
0
Order By: Relevance
“…We extracted data from the METABRIC and TCGA datasets in the cBioPortal (https://www.cbioportal.org accessed on 1 February 2021) database to analyze functional enrichment, and further used the MetaCore Analysis (https://portal.genego.com accessed on 1 February 2021) to explore the downstream network, and p < 0.05 was set as the boundary criterion as we previously described [44][45][46][47][48].…”
Section: Functional Enrichment Analysis Of Psma Family Membersmentioning
confidence: 99%
“…We extracted data from the METABRIC and TCGA datasets in the cBioPortal (https://www.cbioportal.org accessed on 1 February 2021) database to analyze functional enrichment, and further used the MetaCore Analysis (https://portal.genego.com accessed on 1 February 2021) to explore the downstream network, and p < 0.05 was set as the boundary criterion as we previously described [44][45][46][47][48].…”
Section: Functional Enrichment Analysis Of Psma Family Membersmentioning
confidence: 99%
“…The expression of NEK2 in tumor tissues was higher than that in healthy tissues. Moreover, Gangga Anuraga et al revealed that NEK2 is involved in immune infiltration and may serve as a prognostic biomarker for breast cancer progression ( Anuraga et al, 2021 ). Therefore, it may be considered that the increased expression of NEK2 in most human tumors is a common phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…MethSurv ( https://biit.cs.ut.ee/methsurv/ ) is a bioinformatics tool for survival analysis based on CpG methylation patterns, with methylation data of multiple human cancers [ 20 , 21 ]. The CpG methylation status of DCGs and the associations between DCGs methylation, gene expression, and prognosis were revealed by using this tool in our study.…”
Section: Methodsmentioning
confidence: 99%